PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. SECURINDO PACKATAMA INDONESIA - Tini Juartini (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2021)
This study derived from problems where formulation to want to know influence motivation and discipline employees of pt work on performance PT. Securindo Packatama Indonesia. Object the employees of PT. Securindo Packatama Indonesia. It is the type of the kind of research by using the method quantitative research survey and data collection. In this research researchers used primary data obtained directly from respondents uses the chief questionnaire (questions) written given to respondents and distributed to all the employees PT. Securindo Packatama Indonesia. The sample used is a technique that sample saturated sample if all members of the technique was used as a population sample, Methods of data analysis using partially and simultaneous linear regression. It can be concluded that an employee of PT. Securindo Packatama Indonesia need motivation and work to improve their performance and discipline employees so we can achieve the objectives and targets the company well.